Les techniques de sculpture dans l’Antiquité tardive et le haut Moyen Âge - Thierry Gregor; Anne-Bénédicte Mérel-Brandenburg (Les Cahiers de l'École du Louvre)
Stone-carving techniques in Late Antiquity and the Early Middle Ages were very specific. By comparing various works from the Louvre and the Musée Sainte-Croix in Poitiers with the conditions of use of the tools, sometimes particular and original, the paper will describe in detail these specific techniques and the approach to the stone material, always ingenious, of the engravers, sculptors, stone cutters or simply the executors during this pivotal period.